1987
DOI: 10.1021/bi00377a019
|View full text |Cite
|
Sign up to set email alerts
|

Blood coagulation induced by the venom of Bothrops atrox. 2. Identification, purification, and properties of two factor X activators

Abstract: We have characterized and purified the two components of the venom of Bothrops atrox that activate the coagulation factor X. Activator 1 and activator 2 were separated by ion-exchange chromatography but otherwise presented similar characteristics. They consist of a heavy polypeptide of Mr 59,000 and either one or two light chains forming a doublet of Mr 14,000-15,000. They are inactive on synthetic substrates and on prothrombin or fibrinogen and thus appear to act specifically on factor X. They are not sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
3

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(42 citation statements)
references
References 40 publications
3
36
0
3
Order By: Relevance
“…As for factor X, we observed that MooA induced the cleavage of the zymogen heavy chain at Arg 194 -Ile 195 , which led to the formation of enzymatically active factor Xa. A similar pattern of proteolytic activation has also been observed for endogenous factor VII/Tissue factor complex and other SVMPs (Hofmann and Bon 1987b;Takeya et al 1992;Siigur et al 2001;Samel et al 2003;Sun et al 2010).…”
Section: Discussionsupporting
confidence: 67%
“…As for factor X, we observed that MooA induced the cleavage of the zymogen heavy chain at Arg 194 -Ile 195 , which led to the formation of enzymatically active factor Xa. A similar pattern of proteolytic activation has also been observed for endogenous factor VII/Tissue factor complex and other SVMPs (Hofmann and Bon 1987b;Takeya et al 1992;Siigur et al 2001;Samel et al 2003;Sun et al 2010).…”
Section: Discussionsupporting
confidence: 67%
“…With only a few exceptions, efficient activation of factor X critically depends upon the presence of CaCl 2 . Dose-response curves for CaCl 2 typically show a sigmoidal dependency with Hill coefficients ranging from 2.4 to 7.9 [11][12][13]. Since the mechanism of factor X activation by the activator present in Russell's viper venom (RVV-X) is quite well understood and can be regarded as an example for the other venom activators belonging to the group of metalloproteases, we will describe this activator in more detail.…”
Section: Snake Venom Activators Of Factor Xmentioning
confidence: 99%
“…Although in the original publications concerning the activators purified from B. atrox and from Cerastes cerastes venom, it was proposed that the purified activators showed heterogeneity because two light chains were observed on SDS-PAGE [11,32], it is very likely that these activators, like RVV-X, consist of a heavy chain containing the metalloprotease domain and two Ctype lectin light chains held together by disulfide bond(s). Hoffmann and Bon [11] isolated two factor X activators from B. atrox venom, but apart from differences in the purification both activators show similar functional characteristics. In addition, it was noted that these activators cleave the heavy chain of factor X at two additional positions, an activity not seen with RVV-X.…”
Section: Metalloprotease Activatorsmentioning
confidence: 99%
“…The activation effect of factor X by VLFXA was measured by the amidolytic activity of the factor Xa that was formed according to the method described by Hofmann and Bon [29]. Bovine or human factor X was used as substrate for VLFXA.…”
Section: Purification Of Proteasesmentioning
confidence: 99%